Experiment and Analysis of Wedge Cutting Angle on Cutting Effect - Deqiang Yang; Xuguang Wang; Yinjun Wang; Huaming An; Zhen Lei (Advances in Civil Engineering)
In the process of tunnel excavation, large charge wedge cutting blasting is widely used to improve the effect of cut blasting and speed up the excavation rate, which is tantamount to increasing the construction cost. In order to save economic cost and improve cutting blasting effect, wedge cutting models with five different cutting angles were experimented and studied by using concrete materials on the basis of similarity theory analysis. The relationships among cutting depth, blasting volume, blasting fragment, and cutting angle are studied and deduced by the dimensional analysis method. The polynomial fitting of cutting depth, blasting volume, blasting fragment, and cutting angle is carried out according to the experimental data, and the corresponding fitting formula is obtained. The optimum cutting depth, hole utilization rate, blasting volume, and blasting fragment were obtained when the wedge cutting angle was 67° under the same charge. The values were 1.665 × 10−1 m, 92.5%, 8.390 × 10−3 m3, and 49.07 mm, respectively. With the use of TC4850N type blasting vibration meter, the blasting vibrations on the wedge in four directions are tested and analyzed. The results show that when wedge cutting inclination is 65 degrees, the peak vibration velocity is the minimum and the vibration intensity of the wedge cutting inclined side is generally smaller than that of the vertical side. Considering the cutting depth, blasting volume, blasting fragment, blasting vibration hazard, drilling error, tunneling construction cost, and other factors, the 65°∼69° wedge cutting blasting in engineering practice can improve the blasting tunneling rate and increase economic benefits. The experimental results show that the blasting tunneling rate is increased and the economic benefit is increased with the minimum construction tunneling cost, which has certain engineering significance.